(untitled) (Andamios, Revista de Investigación Social, 2024)
This paper focuses on Ignacio Ellacuría’s Philosophy of Historical Reality and aims to highlight its potential against contemporary fatalistic and voluntaristic positions. Both terms —fatalism and voluntarism— respectively condense two reductive conceptions of History and how it proceeds. Moreover, they have dangerous anthropological, psychosocial, and political implications since they prevent the correct diagnosis and treatment of structural problems. We conclude that it is in the structural integration between the historical and the natural, on the one hand, as well as in the ideas of real possibility and functionality, on the other hand, where we find some conceptual keys to combat fatalism and voluntarism.